Investigation of Data Dissemination using Publish Subscribe Approach In Opportunistic Network - Albert, Sanjay Charles (Universiti Malaysia Sarawak (UNIMAS), 2019)
Opportunistic Network is a kind of communication technology that operates on rapid changes network topology. The main challenge in Opportunistic Network is to identify the best path to deliver a message to the target destination. This is due to no definite paths exist between source and destination. On top of that, the communication link is intermittent which contribute to high loss packet. In this situation, flooding is the best way to disseminate information. However, this approach consumes lot of resources and duplication of data. Therefore, there are few types of forwarding technique had been proposed by researchers to provide an efficient data dissemination in opportunistic networks such as history based routing, social based routing, probabilistic based routing and context based routing. Nevertheless, each of this routing has its own limitation. All aforementioned routing categories require an active nodes to push information so that a proper selection can be constructed to produce an efficient routing mechanism. With that, this research enhances Publish/Subscribe (PS) approach as it has strong push element which can be further utilized for efficient data dissemination selection in opportunistic network. Proposing Publish/Subcribe Request based (PSRB) approach which envision to enhance from the PS approach. Implement the comparison attribute in both approach to control the information spreading. Therefore, by implementing this attribute during the data exchange able to minimize the data overhead and delivery delay while maintaining the delivery time. Based on the overall performance, PS approach perform higher percentage compare to PSRB approach on the performance metrics.